Minimalisasi Ongkos Unit Produksi dengan Otomatisasi Proses Operasi - Susandi, Dony; Whydiantoro, Whydiantoro; Hermawan, Dadan Agus (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2016)
Companies are required to meet consumers need with limited capacity and capability of the company. In addition to limited capital, adaptability of technology absorption into the barriers that have an impact on production activities. Material handling activities involving the removal, handling, storage and material control with tools, people or machines. One of the main objectives are to reduce the production cost units through simplification, combination, shortening or eliminating unnecessary process. Programmable Logic Controller (PLC) can be applied to the production process activities (automation), including material handling to make it more efficient and effective so as to reduce the production time. This study consists of several stages, namely stages of identification, data collection and processing analysis and conclusion. the principle of the use of material handling equipment including the planning principle, the principle of standardization, working principle, ergonomic principles, and the principles of automation. This research aims to minimize the cost of the material handling control system using PLC. Some of the data used in the study is the operation process chart, routing sheet, average production time, material removal capacity and frequency, number of employees, the cost of labor, hours of work and rectilinier method used to determine the distance between facilities. The results showed a production unit with process automation (PLC) in material handling Rp. 5.99,- per meter, while production unit using manual labor (human) issued Rp. 8.42,- per meter.